Formation of Intercultural Competence in Teaching the Translation of Economic Texts - Badalova Luiza Kholmamatovna (Genius Journals, 2022)
The given article is considered about teaching a foreign language within the framework of the concept of intercultural learning, which includes not only the acquisition of language skills by the trainee and the development of language skills, but also involves obtaining a background information about the culture, history, traditions, way of life, customs of the countries of the studied language.
Keywords: intercultural competence; the socio-cultural component; translation; modern realities